Attitude, Smoking Behavior, and Physical Activities Toward Diabetes Mellitus-Pulmonary Tuberculosis - Retno Lian Afidah (Universitas Airlangga, 2019)
Background: Every year an average of 9 million people suffer from Tuberculosis and about 2 million people die every year in the world. The Behavior Area is divided into attitudes and actions. Purpose: The purpose of this study was to analyze the relationship between attitude, smoking behavior, physical activity and the incidence of Diabetes Mellitus-pulmonary Tuberculosis. Method: This study was an observational analytic study using a case control matching design. The research sample is 30 case samples and 30 control samples. Results: From the results of the Chi Square analysis, it is known that there is a significant relationship that is the attitude towards pulmonary Tuberculosis disease and physical activity towards pulmonary Tuberculosis (p<0.05) and there is no significant relationship (p>0.05) between smoking behavior towards Pulmonary of Diabetes Mellitus-pulmonary Tuberculosis. Odds Ratio of this study is the attitude towards pulmonary Tuberculosis disease of 3.455 and physical activity of 9.036. Conclusion: the attitude of patients with Diabetus Mellitus towards Pulmonary Tuberculosis and physical activity of patients with Diabetus Mellitus risked the incidence of Pulmonary Tuberculosis.